Implementing success factors for effective strategic plans implementation in public health facilities, in Namibia - Shopati, Abner Kukeyinge; Mitonga, Kabwebwe Honore; Aipinge, Lydia Penomuntu (International Journal Of Community Medicine And Public Health, 2018)
Background: Public healthcare organizations are implementing strategic plans modelling with the supposition that the outcome will be enhancing organizational effectiveness, efficiency and delivered superior healthcare services to its clientele. However, in Practices, a good strategy shall be a call for both actions and blueprint for success in responsive to the need it was formulated to address. The aim of this research is to develop implementation success factors model (ISF) for effective strategic plan implementation in public healthcare organization in developing countries. Methods: The research utilized quantitative approach, a survey design and questionnaire was employed to collect data. The study used Gaskin’s CFA/SEM procedure and applies the SPSS 23 AMOS plugins, pattern matrix model builder (PMMB), master validity (MV), model fit measures (MFM) to validate and determine the interrelationships between variables. Results: Reviewing the literature, 20 variables were identified and implementing success factor (ISF) model with two major factors was developed, CSFs for strategic plan formulation and CSFs for strategic plan implementation. This model, in the order of effect, identified CSFs for strategic plan formulation: structural dimension (0.95), content dimension (0.75), operational dimension (0.34) and context dimension (0.23), CSFs for strategic plan implementation: operational dimension (0.70), structural dimension (0.47), contextual dimension (0.46), content (0.37). Conclusions: The research shows that developing implementation success factors model for effective strategic plan implementation in public healthcare organization in developing countries, it will be plausible to consider CSFs for strategic plan formulation and CSFs for strategic plan implementation. Structural equation modelling/CFA has been run to prove the validity of basic CSFs in this research.